2001
DOI: 10.1136/oem.58.12.786
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from lung cancer among silicotic patients in Sardinia: an update study with 10 more years of follow up

Abstract: Objectives-To evaluate the association between silica, silicosis and lung cancer, the mortality of 724 patients with silicosis, first diagnosed by standard chest x ray film between 1964 and 1970, has been analysed by a cohort study extended to 31 December 1997. Methods-Smoking and detailed occupational histories were available for each member of the cohort as well as the estimated lifetime exposure to respirable silica dust and radon daughters. Two independent readers blindly classified standard radiographs ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Together with other recent reports, including experimental and epidemiological data evaluations [Chan et al, 2000;Hessel et al, 2000;Soutar et al, 2000;Carta et al, 2001;Cocco et al, 2001], the present study provides additional information of interest to further evaluate the association between silica and lung cancer [IARC, 1997;Steenland et al, 2001].…”
Section: Discussionmentioning
confidence: 74%
“…Together with other recent reports, including experimental and epidemiological data evaluations [Chan et al, 2000;Hessel et al, 2000;Soutar et al, 2000;Carta et al, 2001;Cocco et al, 2001], the present study provides additional information of interest to further evaluate the association between silica and lung cancer [IARC, 1997;Steenland et al, 2001].…”
Section: Discussionmentioning
confidence: 74%
“…An update study with 10 more years of followup among Sardinia silicotics was excluded from the analysis because only lung cancer SMR was shown among smoking silicotics (regional rates as reference), and the interaction indices could not be estimated. 45 Except for the studies of Chinese granite workers in Singapore and the refractory brick industry in Mainland, China, 12,42 the occupational exposures involved in the other studies were quite mixed, and might involve concomitant exposures to other occupational lung carcinogens. The cases of silicosis came from silicosis registries for the purpose of compensation 10,13,16,21,22,42,43 or from medical surveillance programs at the workplace.…”
Section: Resultsmentioning
confidence: 96%
“…Five studies reported the risk of lung cancer according to the radiological severity of silicosis (29,31,37,45,47). One was excluded from the analysis because of a lack of data (42).…”
Section: Analysis Of Cohort Studiesmentioning
confidence: 99%